2012
DOI: 10.1111/j.1557-9263.2011.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nocturnal seabird activity and status using acoustic recording devices: applications for island restoration

Abstract: Nocturnal burrow‐nesting seabirds breeding on isolated oceanic islands pose challenges to conventional monitoring techniques, resulting in their frequent exclusion from population studies. These seabirds have been devastated by nonnative predator introductions on islands worldwide. After predators are eradicated, recovery has been poorly quantified, but evidence suggests some nocturnal seabird populations have been slow to return. We evaluated the use of automated acoustic recorders and call‐recognition softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 33 publications
7
114
0
Order By: Relevance
“…ARUs can be an effective method for tracking presence or absence of multiple taxa for monitoring and conservation. ARUs can monitor the success of conservation programs (e.g., activity at seabird colonies after invasive predator eradication; Buxton and Jones 2012). Monitoring can continue uninterrupted as long as ARUs are serviced and batteries and data storage are replenished.…”
Section: Current and Future Applicationsmentioning
confidence: 99%
“…ARUs can be an effective method for tracking presence or absence of multiple taxa for monitoring and conservation. ARUs can monitor the success of conservation programs (e.g., activity at seabird colonies after invasive predator eradication; Buxton and Jones 2012). Monitoring can continue uninterrupted as long as ARUs are serviced and batteries and data storage are replenished.…”
Section: Current and Future Applicationsmentioning
confidence: 99%
“…However it was difficult to estimate the absolute number of animals because the call rate differs between species and even within a species, the call rate being strongly dependent on the particular environmental conditions (Farnsworth, 2005;Farnsworth et al, 2004;Hüppop and Hilgerloh, 2012). Buxton and Jones (2012) found that nocturnal call activity can at least provide information on the relative population density of cave breeding birds. Comparing different methods of bird surveys Buckland (2006) found that the census based on song activity delivered results with a rather poor precision.…”
Section: Introductionmentioning
confidence: 98%
“…On many islands the marking of seabirds or inspection of burrows is logistically not feasible, because birds nest on inaccessible cliffs. As a consequence of the various logistical constraints, the population sizes of many species of storm-petrels, petrels, shearwaters and alcids are very poorly known (Brooke 2004;Croxall et al 2012). The burrow-nesting habit of many species, which directly influences the complexity of population assessments, also contributes to their vulnerability to invasive alien predators, a key threat to seabirds (Croxall et al 2012;Jones et al 2008).…”
Section: Introductionmentioning
confidence: 99%